Analisis Cerita Rakyat Rembang Sebagai Media Pembelajaran Bahasa Indonesia Kelas IV - Annisa Titis Mardiana; Imroatus Sholihah; Nabillah Sitompul (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2021)
Positive character is a good attitude or behavior that is carried out by someone. To show good behavior, one must instill these values from an early age. If children are used to being bad, it is likely that these attitudes or behaviors will carry over into adulthood, making things that are not good in a person. On the other hand, if children are taught and instilled good behavior from an early age, it is hoped that in the future when they grow up, these behaviors will stick with them. The most prominent positive characters in the story are the attitude of maintaining good manners towards others, carrying out God's commands by being religiously obedient, loving each other to others, loving peace and not liking violence, finally being persistent in one thing to bring us to the goal that is right for us positive. Generally, children need an interesting way of delivery so that the message can be well received, through folklore it is hoped that learning will reach the goal so that teaching and learning activities are carried out properly.